PENDIDIKAN MORAL MASYARAKAT JAWA (STUDI NILAI-NILAI PENDIDIKAN MORAL DALAM TRADISI RUWATAN) - Muzhoffar Akhwan; Suyanto Suyanto; Muhammad Roy Purwanto (Millah: Journal of Religious Studies, 2010)
This article aims to describe the ruwatan concepts as a part of the Javanese traditions in the form of educational values. ‘Ruwatan’ is often claimed as a negative tradition that tends to polytheism. However, the fact indicates that ruwatan is still existing in Javanese society tradition until recent ages. Based on the condition, the article tries to explain the positive meaning of ruwatan. Since it has positive meaning, the ruwatan is necessary to preserve. In the tradition, it contains one of moral education methods to educate society in order to make better human beings. The study found some educational values in the tradition, i.e. theological education, philosophical education, and social education.